Identification of novel triazolopyrimidines as potent ?-glucosidase inhibitor through design, synthesis, biological evaluations, and computational analysis - Peytam, Fariba; Norouzbahari, Maryam; Gulcan, Hayrettin Ozan; Hosseini, Faezeh Sadat; Moghadam, Mahdis Sadeghi; Mojtabavi, Somayeh; Foroumadi, Alireza (Nature Portfolio, 2025)
alpha-Glucosidase inhibitors are widely used in the management of type 2 diabetes mellitus (T2DM) by delaying carbohydrate digestion and reducing postprandial blood glucose levels. However, current drugs suffer from limited efficacy and gastrointestinal side effects, highlighting the need for novel inhibitors with improved potency and selectivity. In this study, a novel series of 5,7-diaryl-[1,2,4]triazolo[1,5-a]pyrimidin-6-amines 9a-9t was designed and prepared through an efficient, straightforward synthetic route. Subsequently, they were evaluated for their alpha-glucosidase inhibitory activity, with compound 9s exhibiting the most potent inhibition (IC50 = 24.32 +/- 0.18 mu M), outperforming acarbose by over 30-fold. Enzyme kinetics revealed a competitive inhibition mode, and selectivity assays confirmed minimal alpha-amylase inhibition. Spectroscopic analyses (CD and fluorescence) demonstrated significant conformational changes in alpha-glucosidase upon ligand binding, suggesting structural stabilization and reduced flexibility. Molecular docking and 200-ns MD simulations confirmed persistent hydrophobic and halogen-bond interactions, particularly with residues Phe303, Arg315, and Gln182. Additionally, a BERT-based deep learning model with SMILES augmentation accurately predicted the biological activity of synthesized compounds, validating our computational pipeline. These findings highlight [1,2,4]triazolo[1,5-a]pyrimidines as promising scaffolds for the development of selective and potent alpha-glucosidase inhibitors.
Keywords: [1,2,4]Triazolo[1,5-a]pyrimidine; Triazolopyrimidine; Antidiabetic; alpha-Glucosidase